Former builders and constractors and now the poorest and discriminated pensioners - Soltes, Dusan (Magyar Gerontológia, 2024)
It is a real fact that the generation of the current pensioners during their active productive life have created a lot of various facilities that are still available and successfully utilized for the benefits of citizens. Especially, in former socialist countries they created enormous amounts of facilities that later on during the privatization as a part of the transformation process from the former socialist command economy to current market economy have become the property of the foreign investors.